Personalizing pancreatic cancer medicine: what are the challenges?. (January 2013) - Danielsson, Krissi; Ansari, Daniel; Andersson, Roland
The P4 paradigm for future medicine promises changes in cancer management with improved Prediction of treatment response, Prevention of disease, Personalization of therapy, and Participation by patients. Significant challenges remain for the implementation of the P4 principles for pancreatic cancer, but many strides have been made in the past several years that should facilitate a future in which the disease can be detected at earlier stages and treatments can be customized to target features of a particular patient's disease. This article summarizes the basic molecular biology of pancreatic tumors and the current state of pancreatic cancer treatment, as well as targeted treatments in the pipeline that might enable future personalized pancreatic cancer treatment and prediction of response to treatment. It also discusses possible directions for screening patients at high risk of developing the disease, detecting tumors at earlier stages, and increasing patient involvement in designing treatment.